IMPLEMENTASI PROGRAM PENGUATAN PENDIDIKAN KARAKTER (PPK) DI SDN MANGKANG WETAN 02 KOTA SEMARANG - Rise Aditya Anggraeni; Soedjono Soedjono (GEMA PUBLICA : Jurnal Manajemen dan Kebijakan Publik, 2018)
Character Education Strengthening Program is an educational movement under the responsibility of the education unit to strengthen the character of students through harmonization of the process of heart, taste, thought processing, and sports with involvement and cooperation between education units, families and communities as part of the National Movement Mental Revolution (GNRM). The purpose of this study was to determine the implementation of Character Education Strengthening in Mangkang Wetan 02 Elementary School Semarang City. This study uses a qualitative method, meaning that the main instrument in the study is the researcher himself. Data sources used include primary data sources and secondary data. The results showed that the implementation of Character Education Strengthening in Mangkang Wetan 02 Elementary School Semarang City was quite successful this can be seen from the level of decline in student delinquency but still needs improvement in the phenomenon of the implementation of school-based character education.